2015
DOI: 10.1038/nm.3902
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal transition induces cell cycle arrest and parenchymal damage in renal fibrosis

Abstract: Kidney fibrosis is marked by an epithelial–to–mesenchymal transition (EMT) by tubular epithelial cells (TECs). Here we find that during renal fibrosis TECs acquire a partial EMT program during which they remain associated with their basement membrane and express markers of both epithelial and mesenchymal cells. The functional consequence of EMT program during fibrotic injury is an arrest in the G2 phase of the cell cycle and lower expression of several transporters in TECs. We also found that transgenic expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
736
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 811 publications
(782 citation statements)
references
References 56 publications
34
736
0
12
Order By: Relevance
“…Similarly, it has been shown that resident renal epithelial cells undergo partial EMT that contributes to the interstitial fibrosis phenotype in kidney fibrosis [127,128]. This phenomenon has also been described in cardiac fibrosis [129].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 70%
“…Similarly, it has been shown that resident renal epithelial cells undergo partial EMT that contributes to the interstitial fibrosis phenotype in kidney fibrosis [127,128]. This phenomenon has also been described in cardiac fibrosis [129].…”
Section: Purinergic Signaling Emt and Fibrosismentioning
confidence: 70%
“…Epithelial-mesenchymal transition (EMT) occurs in physiologic processes such as embryogenesis and organ development, and in pathologic conditions including tissue fibrosis and metastasis (78,79). Complement participates in EMT in murine models of renal injury and fibrosis (62,80,81).…”
Section: Complement Activation In Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…Based on the current literature, therefore, it appears likely that de novo EndMT makes a modest contribution to the myofibroblast population in the adult heart. However, studies performed in other organs, such as the kidney, suggest that de novo EMT gives rise to fibroblast-like cells that adopt a partially transitioned state intermediate between epithelial cells and fibroblasts (Grande et al, 2015;Lovisa et al, 2015). This possibility is unexplored in the adult heart but may reconcile the apparent differences between lineagetracing studies on the origin of the cardiac fibroblast.…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%